English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

sqrt 252xy^21 / sqrt 7xy

2007-01-01 14:06:37 · 8 answers · asked by sutherngrlz 1 in Science & Mathematics Mathematics

8 answers

sqrt (252xy^21) / sqrt(7xy)
=sqrt[252xy^21 / (7xy)]
=sqrt(36y^20)
=6y^10

2007-01-01 14:15:35 · answer #1 · answered by sahsjing 7 · 0 0

You need some parenthesis in there
Assuming you mean squrt(252xy^21)/sqrt&7xy)
this is equal to
sqrt((252xy^21)/(7xy))
Simplify the arguement of the ssquare root first:
252/7 = 36
(xy^21)/(xy) = y^20
so you want sqrt (36y^20) = +/- 6 y^10
If I have assumed wrong and the original quesion is sometihng else, you would still begin by combining the radicals since
(sqrt(A))/(sqrt(B)) = sqrt (A/B)
and then simplifying
Be sure and include the +/- with the number

2007-01-01 14:20:50 · answer #2 · answered by Joni DaNerd 6 · 0 0

sqrt(252xy^21) / sqrt(7xy)

=sqrt(252 xy^21 / (7xy)) because sqrt(a) / sqrt(b) = sqrt(a/b)

=sqrt(36 xy^21 / (xy)) because 252/7=36

= sqrt(36 y^21 / y) because the x's cancel

=sqrt(36 y ^20) since one of the y's cancel

= 6 y^10 since the square root of 36 is 6
and the square root of y^20 is y^10 because y^10 * y^10 = y^20 (add the powers)

2007-01-01 14:22:05 · answer #3 · answered by Professor Maddie 4 · 0 0

if by this you mean

(sqrt(252xy^21))/(sqrt(7xy))

you can write it as

sqrt((252xy^21)/(7xy))
sqrt((252/7) * x^(1 - 1) * y^(21 - 1))
sqrt(36y^20)

sqrt(36) * sqrt(y^20)
(-6 or 6) * y^(20/2)

ANS : -6y^10 or 6y^10

2007-01-01 15:26:01 · answer #4 · answered by Sherman81 6 · 0 0

sqrt(a)/sqrt(b) = sqrt(a/b)
So, sqrt 252xy^21 / sqrt 7xy
= sqrt(252xy^21/7xy)
=sqrt(36y^20)
= +/- 6y^10

2007-01-01 14:22:41 · answer #5 · answered by ironduke8159 7 · 0 0

Assuming you mean sqrt(252*x*(y^21)) / sqrt(7*x*y):

sqrt(252*x*(y^21)) / sqrt(7*x*y) = sqrt(252*x*(y^21)/(7*x*y))
= sqrt(36*(y^20)
= 6y^10

2007-01-01 14:17:35 · answer #6 · answered by Anonymous · 0 0

Plug that equation into a google window and it should bring you to a place where you can get some math help.

2007-01-01 14:19:17 · answer #7 · answered by skyboy96 1 · 0 0

Your question is ambiguous. What part of the expression is under the first square root?

2007-01-01 14:14:22 · answer #8 · answered by Northstar 7 · 0 0

fedest.com, questions and answers